GSEPIM: A roadmap for software process assessment and improvement in the domain of global software development. Issue 1 (22nd August 2018) - Khan, Arif Ali; Keung, Jacky; Niazi, Mahmood; Hussain, Shahid; Shameem, Mohammad
Abstract: Software development firms have begun adopting the practice of global software development (GSD). The main reason for the shift toward globalization is the various benefits received by software development firms. However, there are several issues faced by GSD organizations, particularly those associated with software process improvement (SPI). It has been noticed that a formal process improvement approach could assist in successfully executing development activities in GSD. The core objective of this research work is to develop a global software engineering process improvement model (GSEPIM) to assess and improve software process activities in a GSD environment. The proposed model will be developed based on existing models in other domains, an empirical study conducted with GSD practitioners, and an understanding of critical success factors and challenges of SPI. In this study, the first step in the development of GSEPIM is completed by identifying the challenges of SPI in GSD and presenting a solution in the form of a robust framework. Abstract :